Building a Research Culture in Schools: An Analysis of Principals’ Innovative Leadership and Adaptive Strategies - M. Fadil Hafiz (Organon: Journal of Islamic Education Management, 2026)
In the 21st century, the complex demands of global education require schools to transform into dynamic learning organizations, making the establishment of a research and innovation-based ecosystem an institutional necessity. This study aims to analyze the principal’s role in cultivating this ecosystem, identify effective innovative leadership strategies, and explore adaptive solutions to implementation challenges. Utilizing a qualitative library research design, this study conducted a descriptive content analysis of reputable academic literature published in recent years. The findings reveal that successful transformation requires a paradigm shift from conventional administrative management to visionary, innovative leadership. Key strategies include institutionalizing teacher action research through Professional Learning Communities (PLCs), integrating digitalization for transparent quality management, and employing adaptive, transformational approaches to overcome structural constraints. The study highlights that despite significant barriers such as heavy workloads and resource limitations, particularly in peripheral areas, principals can drive sustainable educational quality by leveraging social capital, intrinsic motivation, and collaborative governance.